PREVENTIVE EFFICACY OF TOPICAL APPLICATION OF THE BACTERIAL LYSATES MIXTURE AMONG THE HEALTHY CHILDREN FROM ORGANIZED COLLECTIVES - T.E. Taranushenko; S.Yu. Artemova; Z.N. Goncharuk (Вопросы современной педиатрии, 2007)
The research studied the preventive efficacy of the bacterial lysates mixture (IRS 19) prescribed to the healthy primary school aged children. it shows that the application of this medication has been accompanied by the increase of both absolute and relative amount of neutrophils, macrophages and epithelial cells in the nasal secretion. In the test group, the increase of the above said elements has been noted among fewer children, while their share in the total cell mass not only remained intact, yet quite on the contrary the relative amount of macrophages almost twofold reduced. Changes in the cell contents of the nasal secretion among the healthy children and against the application of the bacterial lysates mixture were associated with the recurrence rate of the acute respiratory infection in the following 4 months of observation. The obtained findings allow one to recommend the given immunomodulator for the prevention of the respiratory diseases among the healthy children from organized collectives.Key words: healthy children, topical bacterial lysates, prevention, acute respiratory infection.